2020
DOI: 10.2337/figshare.12621884
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impaired succinate response to a mixed meal in obesity and type 2 diabetes is normalized after metabolic surgery

Abstract: <div><b><i>Objective</i></b> To explore the meal response of circulating succinate in patients with obesity and type 2 diabetes undergoing bariatric surgery, and to examine the role of gastrointestinal glucose sensing in succinate dynamics in healthy subjects. <b><i><br></i></b></div><div><b><i>Research Design and</i></b> <b><i>Methods</i></b> Cohort I comprised 45 patients with morbid obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…We found that higher circulating succinate levels in patients with severe obesity were associated with a worse metabolic profile, as previously described in other cohorts [12,49]. Specifically, we observed significant positive correlations between circulating succinate levels and waist circumference (r = 0.461, p = 0.001), waist-tohip ratio (r = 0.403, p = 0.005), triglycerides (r = 0.306, p = 0.033), insulin (r = 0.331, p = 0.021), and uric acid (r = 0.423, p = 0.003).…”
Section: Plasma Succinate Inversely Correlates With Fecal Succinate A...supporting
confidence: 87%
“…We found that higher circulating succinate levels in patients with severe obesity were associated with a worse metabolic profile, as previously described in other cohorts [12,49]. Specifically, we observed significant positive correlations between circulating succinate levels and waist circumference (r = 0.461, p = 0.001), waist-tohip ratio (r = 0.403, p = 0.005), triglycerides (r = 0.306, p = 0.033), insulin (r = 0.331, p = 0.021), and uric acid (r = 0.423, p = 0.003).…”
Section: Plasma Succinate Inversely Correlates With Fecal Succinate A...supporting
confidence: 87%
“…Succinate concentrations in the blood are clearly elevated in inflammatory-related health conditions, including obesity and type 2 diabetes [29][30][31][32]. Therefore, we tested the level of succinate in the blood of 8-week treated mice, and our data showed that gemigliptin administration also markedly reduced succinate levels in the serum of the HFHC diet group, which showed significantly higher succinate levels than the control diet group (Fig.…”
Section: Gemigliptin Protected the Liver From Oxidative Stress And Mi...mentioning
confidence: 86%
“…It was generally assumed that SUCNR1 is functionally inactive in healthy tissues, and for many years SUCNR1 was investigated mainly in inflammatory-related conditions [5][6][7][8] , in particular those associated with chronic hypersuccinemia [9][10][11][12] . Recent studies, however, have described that extracellular succinate transiently increases in response to physiological stimuli including exercise 13 , cold exposure 14 or food ingestion, as we recently reported 15 . Succinate thus emerges as a reporter of both tissue stress and metabolism, opening up the possibility of its involvement in other metabolic functions as a hormone-like metabolite 1 .…”
Section: Introductionmentioning
confidence: 54%